The Effect of Use Learning Media on the Economics Outcomes Learning in Tenth Grade Students of Kalam Kudus Christian School Pematangsiantar During the Pandemic Period - Susy Alestriani Sibagariang; Holmes Rajagukguk (Institute of Computer Science (IOCS), 2021)
This study aims to reveal The Effect of Use Learning Media on the Economics Outcomes Learning in Tenth Grade of Students Kalam Kudus Christian School Pematangsiantar During the Pandemic Period. The method used in this research is the experimental method. The research subjects were students of class X5 as an experimental class consisting of 50 students and class X2 as a control class consisting of 50 students. The instrument used is test results. Learning outcome tests are used to measure student learning outcomes. In testing the hypothesis the statistical test